2021
DOI: 10.1038/s41467-021-21272-7
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of structure-forming systems

Abstract: Structure-forming systems are ubiquitous in nature, ranging from atoms building molecules to self-assembly of colloidal amphibolic particles. The understanding of the underlying thermodynamics of such systems remains an important problem. Here, we derive the entropy for structure-forming systems that differs from Boltzmann-Gibbs entropy by a term that explicitly captures clustered states. For large systems and low concentrations the approach is equivalent to the grand-canonical ensemble; for small systems we f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…Questions like the definition of free energies or the possible need of extensivity, which have to be answered in order to progress towards a complete and consistent thermodynamic picture remain, however, open. For tentative answers to those questions, connections to early proposals could be drawn, both on the thermodynamic grounds; see, e.g., [36,65,66], and from the perspective of entropy characterization; see, e.g., [37,44,46,53,54]. In this paper we meet an equivalence relation underlying compact scales, which allows us to transform between compact scales that do not differ too strongly, i.e., not more than by a power, without essentially changing the structure of the typical set sequence, a fact that one can utilize to give the entropic functional particular properties.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Questions like the definition of free energies or the possible need of extensivity, which have to be answered in order to progress towards a complete and consistent thermodynamic picture remain, however, open. For tentative answers to those questions, connections to early proposals could be drawn, both on the thermodynamic grounds; see, e.g., [36,65,66], and from the perspective of entropy characterization; see, e.g., [37,44,46,53,54]. In this paper we meet an equivalence relation underlying compact scales, which allows us to transform between compact scales that do not differ too strongly, i.e., not more than by a power, without essentially changing the structure of the typical set sequence, a fact that one can utilize to give the entropic functional particular properties.…”
Section: Discussionmentioning
confidence: 99%
“…random variables, the Gibbs-Shannon entropic functional arises naturally in the characterization of the typical set [24,25], establishing a clear connection between thermodynamics and phase space occupation. In systems/processes with collapsing or exploding phase spaces, path dependence or strong internal correlations [4,[18][19][20][21][32][33][34][35][36][37], the phase space may grow super-or sub-exponentially, and the emergence of the Shannon-Gibbs entropic functional derived from phase space volume occupancy considerations is no longer guaranteed. The same situation may arise in cases dealing with non-stationary information sources [38][39][40][41][42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This model was proposed to study the structure-forming systems ranging from the atoms that build molecules to the self-assembly of colloidal amphibolic particles. It was shown that the model exhibits a first-order phase transition when the number of "molecule states" is high [25]. An interesting is the case of a hybrid Potts model [26].…”
Section: Introductionmentioning
confidence: 99%
“…Some examples for different process classes include i.i.d. processes, exchangeable and polynomial mixture processes [ 20 ], Polya processes [ 21 ], sample space reducing processes [ 6 ], and processes describing structure forming systems [ 22 ].…”
Section: Introductionmentioning
confidence: 99%